2007
DOI: 10.1007/978-0-387-72005-0_2
|View full text |Cite
|
Sign up to set email alerts
|

The Four Most Common Pediatric Immunodeficiencies

Abstract: Other than the physiologic hypogammaglobulinemia of infancy, 80% of the confirmed immunodeficiencies consist of four syndromes: transient hypogammaglobulinemia of infancy (THI), IgG subclass deficiency, partial antibody deficiency with impaired polysaccharide responsiveness (IPR), and selective IgA deficiency IgAD. None are life threatening, all can be readily managed, and many recover spontaneously. An exact incidence of these disorders is not known. A summary of immunodeficiency registries in four countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 22 publications
1
33
0
2
Order By: Relevance
“…A ntibody production defects are the most common category of pediatric primary immunodeficiencies (PIDs) (1,2). The hallmark of these immunodeficiency conditions is the defective production of antigen-specific antibodies that are an indispensable element of the adaptive immune response to pathogens (3,4).…”
mentioning
confidence: 99%
“…A ntibody production defects are the most common category of pediatric primary immunodeficiencies (PIDs) (1,2). The hallmark of these immunodeficiency conditions is the defective production of antigen-specific antibodies that are an indispensable element of the adaptive immune response to pathogens (3,4).…”
mentioning
confidence: 99%
“…Brazil reported 50 cases of deficiency complement, followed by 13 reports of Argentina (Leiva et al, 2007). Like others studies, predominantly antibody deficiency was the principal PID observed in Latin America, Australia (Baumgart et al, 1997;Kirkpatrick et al, 2007), China (Zhao et al, 2006;Wang et al, 2011), Egypt (Reda et al, 2009), French (CEREDIH, 2010, Hong Kong (Lam et al, 2005), Iran (Aghamohammadi et al, 2002;Farhoudi et al, 2005;Rezaei et al, 2006), Italy (Luzi et al, 1983), Kuwait (AlHerz, 2008), Netherland (Zegers et al, 1994), Norway (Stray-Pedersen et al, 2000), Poland (Bernatowska et al, 1998), Republic of Ireland (Abuzakouk et al, 2005), Spain (Matamoros et al, 1997;Milá et al, 2001), Swiss (Ryser et al, 1998), Taiwan (Lee et al, 2011), Thailand (Benjasupattananan et al, 2009), Tunisia (Bejaoui et al, 1997) and USA (Javier et al, 2000;Stiehm, 2007), Studies in other countries reveled major number of granulocyte dysfunction in India (Verma et al, 2008), and Combined T-and B-cell Immunodeficiency in Turk (Shabestari et al, 2007).…”
Section: Latin American Group Of Immunodeficiencymentioning
confidence: 99%
“…In addition, IgG subclass deficiency is among the more common immunodeficiencies in pediatric populations, resulting in increased rates of particular infections (18,19).…”
Section: Introductionmentioning
confidence: 99%